Multiple Path Particle Dosimetry (MPPD) Model Total Dust Among Mineral Ore Processing Workers - Muhamad Rizky Yudhiantara; Edi Karyono Putro; Prayoga Kara; Anthony Andorful Manuel; Nurulia Hidayah; Arif Susanto (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Mineral ore processing generates dust, which poses a significant health risk to workers due to prolonged exposure. The aerodynamic properties of this dust allow it to be inhaled and deposited deep within the respiratory tract, increasing the risk of impaired respiratory function. This study aimed to quantify and assess the health risk associated with respirable dust exposure among workers in mineral ore processing areas using the Multiple Path Particle Dosimetry (MPPD) Model. The MPPD model was used to estimate the deposition of dust particles in various regions of the respiratory tract. A constant scenario with the average respirable dust concentration values was used. The values of breathing parameters, such as upper respiratory tract volume, functional residual capacity, breathing frequency, and tidal volume, refer to The International Commission on Radiological Protection (ICRP). Personal respirable dust monitoring data from 2021 to 2024 were analyzed to calculate the total deposition, regional deposition, and deposition fraction for each generation of airways. A cross sectional analysis was conducted on a cohort of 30 male laborers, designated as the directly exposed group. Instruments and procedures used for assessing personal exposure to respirable dust were executed by the NIOSH 0600 standard methodology, employing an SKC Cyclone in conjunction with a personal air sampler, characterized by an airflow rate of approximately 1.9 to 2.0 lpm. The average personal respirable monitoring concentration over the past four years (2021 -2024) was 0,2391 mg/m3, with annual averages of 0,2835 mg/m3, 0,2626 mg/m3, 0,1441 mg/m3, and 0,2661 mg/m3, generally within the permissible exposure limit (PEL). The MPPD model simulation results for 2021 showed a maximum mass deposition rate of 2,74 x 10-3 μg/min and a maximum mass deposition per area of 7,374 x 10-3 μg/m2. Particle size, shape, density, and airflow velocity were identified as the key factors influencing dust deposition. Understanding dust distribution within the respiratory tract can provide more effective recommendations for controlling dust exposure and implementing a respiratory protection program (RPP) for workers in the mineral ore processing industry.